Bruxism as a Consequence of Stress and Movement Disorders: Brief Review - Heboyan, Artak; Karobari, Mohmed Isaqali; Alwadaani, Abdullah Hamed; Marya, Anand; Zafar, Muhammad Sohail (European Journal of General Dentistry, 2022)
Bruxism is considered to be an unusual repetitive movement syndrome, which is described as involuntary gnashing of teeth. The condition is classified as sleep bruxism (SB) and awake bruxism (AB). The objective of the study was to review the current literature on bruxism and its potential relation to stress and movement disorders. Factors causing bruxism are numerous. It has been found that people suffering from stress are more prone to the condition than healthy subjects. Awake bruxism is frequently observed in subjects with hyperkinetic movement disorders and it can be associated with anxiety, which involves the limbic part of the basal ganglia. However, further studies should be conducted to interpret the link more thoroughly.
Keywords: teeth grinding; parasomnia; parafunction; repetitive jaw movement; mastication muscle activity